Factors causing the gender pay gap - Ghasemi, Bardia; Černá, Daniela; Legnerová, Kateřina, 1965-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
The research at hand aims to provide a comprehensive perspective on the factors causing the gender pay gap in European Union, especially in hierarchical organisational structures. Moreover, the study includes the identification of the factors and the consequences that they cause in the total wage distribution structure. Additionally, it provides top management with possible solutions regarding this issue and how to tackle the challenges in different stages of employees' career cycle from recruitment to promotion.
Vedoucí práce: Daniela Černá
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses